Mediating Function of Sustainable Agriculture in The Impact of FinTech on AI-Based Green Marketing - Aditya, Ascasaputra; Artha, Bhenu; Hadi, Antonius Satria; Bahri, Bahri; Sari, Niken Permata; Sari, Utami Tunjung; Asri, Cahya Purnama (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Global sustainability agendas, especially in the agricultural sector, are being advanced by the convergence of green marketing, sustainable agriculture, and technological innovation. Green marketing orientation gauges an organization's commitment to putting strategic, tactical, and internal procedures and activities into place with the goal of developing, communicating, and delivering goods and/or services with the least amount of environmental impact. FinTech is the use of cutting-edge digital technologies, like blockchain, digital credit, mobile banking, and alternative data analytics, to provide financial services, particularly in areas where traditional systems are still insufficiently advanced or exclusive. By improving efficiency, increasing access, lowering transaction costs, and promoting financial inclusion, all of which are essential components of sustainable development, FinTech has quickly upended traditional financial infrastructures. The purpose of this study is to determine the influence of fintech on sustainable agriculture and ultimately affect artificial intelligence (AI)-based green marketing. This research uses theoretical literature review as a research method. Authors found that fintech affects sustainable agriculture, and AI-based green marketing affected by sustainable agriculture. Digital finance has emerged as a transformative force in the agricultural sector, reshaping how farmers, agribusinesses, and intermediaries access and manage financial services. The agricultural value chain, which encompasses production, processing, distribution, and retail, has historically faced challenges related to inefficiency, lack of transparency, and limited access to credit. By integrating digital technologies such as mobile banking, blockchain, and digital payment systems, financial transactions within agriculture are becoming more transparent, accessible, and efficient.